Improving Literacy Skills and Memorisation of Short Verses in Early Childhood - Haryanto, Sri; Poncowati, Srikandi Dwi; Pattiasina, Petrus Jacob; Astafi, Riki; Nugroho, Wahyu (Al-Hijr: Journal of Adulearn World, 2024)
Reading and understanding the Qur'an is obligatory for Muslims, for this reason, instilling a culture of reading and memorizing selected short surahs will be better if done as early as possible.The purpose of this study is to discuss literacy skills and mastery of memorizing short verses in early childhood.This research method uses a qualitative type through surveys and in-depth interviews via WaatsApp.The subjects of this research are teachers who teach and students who take early childhood education (PAUD). The results of this study include an overview of improving literacy skills and mastery of short verses in early childhood.This study concludes that the ability to memorize short verses in early childhood is very diverse, and mastery of short verses still needs guidance and must be improved literacy skills on short verses.The limitation in this study is that researchers have not been able to examine more deeply the literacy skills possessed by each early childhood.Therefore, researchers hope that future researchers can conduct research that aims to examine more deeply the ability of early childhood in understanding short verses.